An Efficient Microcontroller Based Sun Tracker Control for Solar Cell Systems - E.M.H. Arif; J. Hossen; G. Ramana Murthy; Jesmeen M. Z. H.; J. Emerson Raja (Institute of Advanced Engineering and Science, 2019)
The solar energy is fast becoming a different means of electricity resource. Now in world Fossil fuels are seriously depleting thus the need for another energy source is a necessity. To create effective utilization of its solar, energy efficiency must be maximized. An attainable way to deal with amplifying the power output of sun-powered exhibit is by sun tracking. This paper presents the control system for a solar cell orientation device which follows the sun in real time during daytime.